Cardiac arrest in pediatric patients with congenital heart diseases undergoing cardiac catheterization: A retrospective study - Prasert Sawasdiwipachai (2019)
© 2018, Medical Association of Thailand. All rights reserved. Objective: Cardiac catheterizations are frequently performed in patients with congenital heart diseases. Cardiac arrest is the serious complication that may affect the overall outcomes. The study was designed to report the incidence of in-procedure cardiac arrest and potential contributing factors. Materials and Methods: We conducted a single-center, retrospective cohort study by chart review in pediatric patients undergoing cardiac catheterization in a large tertiary referral cardiac care center between January 2011 to June 2016. Patient demographic data, diagnosis, incidence of cardiac arrest, outcome of cardiopulmonary resuscitation [CPR] and their final disposition were collected and analyzed. Results: A total of 726 catheterizations performed during the study period and reported incidence of cardiac arrests were 14 cases (1.9%). Successful CPR in 11 patients (84.6%, 1 patient was with Do Not Resuscitate status), but only 8 patients (57.1%) survived to hospital discharge. Univariate analysis identified the following factors to be contributing to cardiac arrest: age <1 year, weight <5 kg, American Society of Anesthesiologists [ASA] classification III-V, children with other comorbidities, cyanotic type defect and emergent catheterization. The incidence of cardiac arrest during pediatric catheterization remains high, Special precautions should be exercised for patients at risk.